AB0043 THE IMBALANCE OF T FOLLICULAR REGULATORY CELL AND T FOLLICULAR HELPER CELL IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Su, R.; Wang, Y. Y.; Hu, F. Y.; Zheng, X.; Liu, Y.; Li, X.; Wang, C.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease which can lead to severe joint damage and disability.The relationship between antibodies and rheumatoid arthritis has long been well established. Recently, many studies have found that T follicular regulatory cells(Tfr) and T follicular helper cells (Tfh) are closely related to antibody generation on lymphoid follicular germinal centers (GCs) [1-2] . Tfr cells can inhibite the GC reaction and suppress production of high-affinity antibodies. The dysregulation of Tfh cells can lead to the production of autoantibodies by B cells. Objectives: To examine the expression of circulating T follicular regulatory cell (Tfr) and T follicular helper cell and its subsets(Tfh1 Tfh2 Tfh17) in RA patients and healthy control group. Methods: Level of Tfr and Tfh1, Tfh2 and Tfh17 cells in the peripheral blood of 17 new RA patients, 30 treated RA patients and 18 healthy controls were deceted by flow cytomery. All patients were hospitalised at the Department of Rheumatology, Second Hospital of Shanxi Medical University. Results: We found that the level of Tfr (CD3+CD4+CD25+CXCR5+FOP3+) percent(P=0.020), in the peripheral blood in RA patients were significantly decreased compared with healthy controls. The percent of Tfh (CD3+CD4+CXCR5+CD45RA-) ( P =0.039)and Tfh17 (CD3+CD4+CXCR5+CD45RA-CXCR3-CCR6+) ( P =0.000)were increased, but there are no statistical difference about Tfh1(CD3+CD4+CXCR5+CD45RA-CXCR3+CCR6-)( P =0.558) and Tfh2 (CD3+CD4+CXCR5+CD45RA-CXCR3-CCR6-) percent( P =0.079). We compared the above indicators between new and treated RA patients, and the results indicated that the Tfr( P= 0.013), Tfh ( P= 0.002) and Tfh1( P= 0.034) were significantly increased in the new RA patients compared to the treated RA patients, there were no differences between the two groups in Tfh2( P =0.419) and Tfh17 percent( P =0.124). Conclusion: Our results indicated that disorder of Tfr and Tfh subsets were involved in RA, restoring the Tfr/Tfh balance may be the potential therapeutic targets. References: [1]Deng J, Wei Y, Fonseca VR, Graca L, Yu D.T follicular helper cells and T follicular regulatory cells in rheumatic diseases[J].Nat Rev Rheumatol. 2019, 15(8):475-490. [2]Chen Liu, Dongwei Wang, Songsong Lu, et al.Increased Circulating Follicular Treg Cells Are Associated With Lower Levels of Autoantibodies in Patients With Rheumatoid Arthritis in Stable Remission.Arthritis Rheumatol. 2018, 70(5):711-721 Disclosure of Interests: None declared